Pemutusan mata rantai penyebaran virus Covid-19 dengan pembagian masker, alat kebersihan, spanduk di Pasar Klender Jakarta - Rayhana, Rayhana; SF, Fanny; Sugiarto, Sugiarto; Heriyanto, Heriyanto; Effendi, Rusdi; Shabariah, Rahmini; SG, 7Hardiman; A, Belva Elrica; Rizqi, Fitri Nur; Adib, Muhammad (Abdi Masyarakat, 2021)
Covid-19 is caused by SARS-CoV-2 which is spread through the air and enters the body through the respiratory tract. It spreads so fast that it becomes a pandemic in a short period of time. The impact of the Covid-19 pandemic is felt by all groups, especially people whose daily work is interacting with other people, thus requiring them to obey health protocols. There is also community interaction in the market which requires them to interact with one another. The chain of spreading Covid-19 must be broken immediately by complying with health protocols. In order to help the government break the chain of the spread of Covid 19 by doing community service at Klender Market, which is one of the main markets in DKI Jakarta, especially East Jakarta. We distributed masks, hygiene kits and banners to invite the public, especially those who interact at Klender Market, to comply with health protocols.